PERAN FINANCIAL WELL-BEING DAN AKSES PERMODALAN DALAM MENINGKATKAN KINERJA KEUANGAN USAHA MIKRO DI KECAMATAN KADIPATEN TASIKMALAYA - Dyah Ciptaning Lokiteswara Setya Wardhani; Iis Amanah Amida; Siti Nurjamilah (LPPM STIE YKPN Yogyakarta, 2025)
This study aims to analyze the influence of financial well-being and access to capital on the financial performance of microenterprises. Microenterprises play a vital role in the local economy but often face financial constraints that hinder their sustainability and growth. Using a quantitative approach, primary data were collected through structured questionnaires from 100 microenterprise owners in [insert location]. Financial well-being was measured based on perceptions of personal financial management capabilities, while access to capital included the ease, sources, and frequency of obtaining business funding. Financial performance was assessed using indicators such as income, revenue growth, and business profitability. Multiple linear regression analysis revealed that both financial well-being and access to capital have a significant and positive effect on microenterprise financial performance. These findings highlight the importance of strengthening personal financial capacity and expanding access to capital in enhancing the resilience and development of micro, small, and medium-sized enterprises (MSMEs) at the local level.